Pemberdayaan Kader Posyandu dalam Meningkatkan Tumbuh Kembang Balita dengan Media Cetak Buku Saku “Teman Bunda” - Nikmah, Nurun; Qomari, Selvia Nurul; Antina, Rila Rindi (Universitas Muhammadiyah Gresik, 2025)
Growth and development are phases that every individual will go through. It is essential to pay attention to factors that can influence the process of growth and development. The success of a toddler’s growth and development depends not only on nutrition but also on the knowledge of those around the toddler. The understanding of the growth and development process will help mothers to be able to maximize the growth and development of their toddlers. Besides, since cadres are the community members tasked with promoting health in the village, they also need to be knowledgeable in this area. One of the efforts to enhance the knowledge of cadres was carried out by providing education using the Buku Saku